ValueDecisions, a web app to support decisions with conflicting objectives, multiple stakeholders, and uncertainty. (April 2022) - Haag, Fridolin; Aubert, Alice H.; Lienert, Judit
Abstract: Complex environmental and public policy decisions profit from structured procedures such as multi-criteria decision analysis (MCDA). To support such decisions, the new open source application ValueDecisions provides advanced analysis and visualization with no programming expected from users. Based on multi-attribute value theory (MAVT), it offers analysis for decisions with conflicting and interacting objectives, multiple stakeholders, and uncertain consequences of options. Programmed in R, the shiny web framework makes it accessible via a graphical user interface in the browser. We exemplify using ValueDecisions for a wastewater infrastructure planning case in the Paris region. We surveyed preferences of 655 citizens and conducted sensitivity analysis of preference parameters. The best management options were robust across a range of preference profiles and assumptions. To evaluate the app, we developed a novel usability test based on the ISO standard for software quality and surveyed students using ValueDecisions for case studies. Graphical abstract: Image 1 Highlights: ValueDecisions is a novel web app to support environmental MCDA. Non-linear and non-additive preferences can be modeled. Decision models and their sensitivity can be explored interactively. We operationalize a new usability test to evaluate the app. Results for an urban water management case were robust to preference changes.